Fermi level pinned molecular donor/acceptor junctions: reduction of induced carrier density by interfacial charge transfer complexes. Issue 43 (3rd August 2020) - Beyer, Paul; Meister, Eduard; Florian, Timo; Generalov, Alexander; Brütting, Wolfgang; Koch, Norbert; Opitz, Andreas
Abstract : Charge transfer complex (CPX) formation at a donor–acceptor interface reduces the amount of Fermi-level pinning induced interfacial charge transfer. Abstract : Increased hole density in an electron donor-type organic semiconductor can be achieved by deposition of a strong acceptor-type molecular layer on top, and has been shown to enable adjusting the carrier density in organic field effect transistors (OFETs). This interfacial charge transfer is due to simultaneous Fermi level ( E F ) pinning of the donor's highest occupied level and the acceptor's lowest unoccupied level. Here, we investigate the electrical properties of such an E F -pinned junction formed by diindenoperylene (DIP, as donor) and hexafluoro-tetracyano-naphthoquinodimethane (F6, as acceptor) in OFETs, as well as its electronic properties by photoelectron spectroscopy and electrostatic modelling. We find that, in addition to the E F -pinning induced integer charge transfer across the interface, DIP and F6 form charge transfer complexes (CPXs) at their junction. The molecularly thin CPX interlayer acts as insulator and significantly reduces the density of carriers induced on either side of the junction, compared to a scenario without such an interlayer. CPX formation is thus unfavourable for the effectiveness of controlling carrier density at molecular donor/acceptor junctions by E F -pinning.